Reversal of Folate Malabsorption in Tropical and Non-tropical Sprue by Calf Jejunum. Issue 5616 (24th August 1968) - Baker, H.; Frank, O.; Ziffer, H.; Feingold, S.; Cintron-Rivera, A. A.
Abstract : In eight patients with folic acid malabsorption the malabsorption was reversed only when a combination of either 250 mg. of lyophilized human jejunal juice or 5 g. of lyophilized calf jejunum with 5 mg. of synthetic folic acid was fed; calf liver was ineffective. The factors in calf jejunum that re-established folic acid absorption were heat-stable and did not form polyglutamyl folates on previous incubation with folic acid.